The effect of globalization and credit market imperfections on the incidence of child labour. Issue 8 (7th August 2017) - Fatima, Ambreen
Abstract : Purpose: The purpose of this paper is to explore the effect of globalization and credit market imperfections on child labour. Design/methodology/approach: Analysis is based on cross-country regression framework, incorporating 129 developing countries for the period 1970-2010. Findings: The findings indicate that countries that are more open to trade and having higher foreign direct investment inflow have lower incidence of child labour. As child labour in export-related industries is hard to find, trade sanctions may not have a significant effect on child labour. Further study concludes that income of the bottom quartile of the population is the best representation of the income of the poor when studying child labour. Research limitations/implications: The study uses the data compiled by International Labour Organization (ILO). Though much of the variation in the data is because of the adjustments made by ILO, this is the only comparable cross-country estimates available. Hence in the absence of the cross-country comparable estimates, many empirical studies have used this data set (e.g. Cigno et al., 2002; Dehejia and Gatti, 2002; Rogers and Swinnerton, 2001). This study acknowledges this limitation but again in the absence of any comparable estimates, the assessment is also based on this data set. Originality/value: Study contributes in the literature by comparing the effect of export and trade and by exploring the effect of an alternate measure of the income, estimated by using Gini coefficient, on child labour. Further studies exploring the effect of globalization did not explore the presence of imperfect credit market, however, this study has explored the effect of credit market imperfections as well.